The impact of social entrepreneurial antecedents on social entrepreneurial intentions of post-graduate students : the moderating role of entrepreneurial self-efficacy - Mamabolo, Anastacia (University of Pretoria, 2023)
Mini Dissertation (MBA)--University of Pretoria, 2022.